COVER CROPS USED AS GREEN MANURE IMPROVED SOIL FERTILITY AND SOIL C STOCKS IN A TROPICAL SANDY SOIL - Nascimento, Gislaine dos Santos; Souza, Tancredo; da Silva, Lucas Jónatan Rodrigues; Laurindo, Lídia Klestadt (Revista Valore, 2023)
The use of cover crops as green manure was studied in a 6-year field experiment in a tropical sandy soil. Our aim was to assess whether Facabeae and Poaceae plants used as green manure can improve soil fertility and soil C stock by their biomass production and incorporation into soil profile. We compared the soil chemical properties, the aboveground and belowground growth rate of ten different cover crops used as green manure in a long-term field experiment. Our findings showed that C. ensiformis and N. wightii showed the highest aboveground and belowground growth rate, respectively. The incorporation into soil profile with B. decumbens and P. glaucum as green manure improved both the soil Ca2+, and K+ contents. While the highest values of available P were found on plots where C. ensiformis was cultivated. For soil organic carbon stocks, we found the highest values on plots where M. pruriens and D. lablab were cultivated. Our results emphasised the importance to consider the Fabaceae plants (e.g., C. ensiformis, D. lablab, M. pruriens, and N. wightii) as soil conditioners against soil erosion, soil organic matter loss, low P fertility, and plant nutrient leaching. On the other hand, the Poaceae species (e.g., B. decumbens, and P. glaucum) can be considered as potential promoters of soil Ca2+ and K+ contents in tropical sandy soils.